2013
DOI: 10.3109/10253890.2013.789015
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress and biological risk: is the link stronger in Russians than in Taiwanese and Americans?

Abstract: Allostatic load theory implies a relationship between exposure to psychological stress and multi-system physiological dysregulation. We used data from population-based samples in Russia (Moscow), Taiwan, and the United States (US)—which are likely to vary widely with respect to levels of stress exposure and biological markers—to determine the magnitude of the association between perceived stress and physiological dysregulation. The measure of overall dysregulation is based on 15 markers including standard card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 44 publications
(54 reference statements)
1
17
0
3
Order By: Relevance
“…Moreover, other Asian studies have shown similar or different tendencies for the determinants of AL (Hu et al, 2007). However, at this point, it remains difficult to determine whether the similarities or differences in the associations between SES or lifestyle behaviors and AL are due to the genetic background or to cultural factors (Glei et al, 2013), and additional studies focusing on different ethnicities shall be conducted to clarify this point.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other Asian studies have shown similar or different tendencies for the determinants of AL (Hu et al, 2007). However, at this point, it remains difficult to determine whether the similarities or differences in the associations between SES or lifestyle behaviors and AL are due to the genetic background or to cultural factors (Glei et al, 2013), and additional studies focusing on different ethnicities shall be conducted to clarify this point.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived stress involves the feelings or thoughts that individuals have regarding the extent of the stress they are experiencing at a given time. Perceived stress is significant for its biological, emotional, and physical consequences, including cardiovascular disorders, diseases related to poor immunological function, sleep problems and depression [8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Low SES has been linked to greater exposure to acute and chronic stressors and to greater perceived stress (Cohen and Janicki-Deverts, 2012), and stress has been found to be related to inflammation in numerous studies (Black and Garbutt, 2002; Hänsel et al, 2010). Perceived stress has been found to be associated with biological dysregulation in this sample (Glei et al, 2013b), and the strength of this association appears to be higher than in other countries; future work on stress and mortality is planned by the SAHR team.…”
Section: Discussionmentioning
confidence: 71%